Implementation of Environment Management System in Manufacturing Industry : Investigating the Challenges and Mechanism to Address Challenges - Veera Kumar, Mohan; Tonga, Noweg (Kalpana Corporation, 2022)
An environmental management system (EMS) is considered a systematic approach, that is taken by the organization to manage all the issues related to the environment. It includes measuring the performance and taking appropriate action that automatically enhances the value of an organization and is beneficial for both organization and environment. Abu Dhabi is under stress because of rapid urbanization, that is related to land reclamation and construction breakwater. There are several manufacturing units and their activities in Abu Dhabi, UAE that have affected the environment adversely by reducing the quality of air and water and productivity of the ecosystem. As a result, the EMS helps to preserve national resources, such as oil, water to maximize productivity and reduce waste of most resources. Therefore, the present study aims to propose the measures/structure to overcome the challenges of the effective implementation of environmental management system (EMS) by the manufacturing industries in the Emirate of Abu Dhabi, UAE. The factors leading towards the adoption of EMS within the manufacturing industries in UAE and evaluating the current status in the implementation of EMS by such manufacturing industries in UAE has been determined. In order to reach this objective, a quantitative research method has been followed that uses 4–point Likert scale based close-ended questionnaires as primary data and journals, articles, books, etc., has been used as secondary data. Simple random sampling method has been used and the questionnaire has been distributed among 475 individuals with different levels, such as management staff and operational staff from the different manufacturing industries in Abu Dhabi, UAE. SPSS analysis has been used for data analysis tools involving Chi-square tests. The results and findings have been illustrated as per the data analyzed in the study. Also, the limitations and conclusions have been represented for the given research.